2020
DOI: 10.21203/rs.2.12989/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unsafe child feces disposal status in Ethiopia: what factors matter? analysis of pooled data from four demographic and health surveys

Abstract: Background: The only safest way to dispose of a child’s feces is to help the child use a toilet or, for very young children, to put or rinse their feces into a toilet; whereas all other disposals are considered unsafe (feces put/rinsed into a drain or ditch, bush or thrown into the garbage, buried or left on the ground, and not disposed of). The study aims to determine the magnitude and factors associated with unsafe child feces disposal in Ethiopia.Methods: The study is cross-sectional in nature and based on … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
3
2
Order By: Relevance
“…Those from rich households were less likely to dispose of stool as compared with those from the poor wealth quantiles. Although many studies have revealed that, the highest wealth quantile increases the likelihood of safe waste disposal (16,20,22,30). The ndings of our study are in contrary to those ndings.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Those from rich households were less likely to dispose of stool as compared with those from the poor wealth quantiles. Although many studies have revealed that, the highest wealth quantile increases the likelihood of safe waste disposal (16,20,22,30). The ndings of our study are in contrary to those ndings.…”
Section: Discussioncontrasting
confidence: 99%
“…The prevalence of safe stool disposal among mothers whose child was aged below two years of age was 56.3%( 95%CI: 54.5%, 58.1%)). The nding of the study is higher than studies done in Eswatini, Ethiopia, Bangladesh, India, and Orissa (3,15,20,23,24). On the other hands, the nding of the current study is lower than the study conducted in Malawi, Cambodia and Sub-Saharan Africa (19,25,26).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Mothers' access to information through mass media (television and radio), and ANC attendance may enhance safe children's faeces disposal practice. Several authors [19,23,42] have explained that women exposed to media and those who attend ANC are more likely to have information on positive attitudes and may value the importance of safe disposal of children's stools. Other scholars have also postulated that mothers who have exposure to media and those who attend ANC are more exposed and in a better position to understand the causes of childhood illnesses and consider the practice of hygienic behaviours, such as safe disposal of children's stool and other childcare practices (e.g., good grooming), as significant in protecting their children from illness [19,50].…”
Section: Plos Onementioning
confidence: 99%
“…Hence, gathering empirical evidence is essential, considering the challenges with sanitation practices in a number of sub-Saharan African countries [8]. Moreover, in examining the predictors of safe disposal of children's stool, only few studies [19][20][21][22] used nationally-representative surveys and multilevel modelling [19,20,23] to better account for the hierarchical data structure of the surveys. To the best of our knowledge, there has not been any multi-country study on the predictors of safe stool disposal.…”
Section: Introductionmentioning
confidence: 99%